The detrimental molten pool narrowing phenomenon in wire feed laser beam welding and its suppression by magnetohydrodynamic technique. (1st September 2022) - Meng, Xiangmeng; Artinov, Antoni; Bachmann, Marcel; Üstündağ, Ömer; Gumenyuk, Andrey; Rethmeier, Michael
Highlights: A unique molten pool narrowing phenomenon is found by real-time metal/glass observation and reproduced numerically by a multi-physical model. The detrimental effects of the molten pool narrowing on the element transport are identified and analyzed. By introducing an external oscillating magnetic field, the narrowing phenomenon is suppressed successfully, achieving a better material mixing. The mechanism of the beneficial effect from the MHD technique is revealed by a parametric study. Abstract: Element transport in the wire feed laser beam welding (WFLBW) is directly determined by the molten pool shape and thermo-fluid flow therein. In this paper, an untypical molten pool profile, i.e., elongated at its top and bottom but narrowed at the middle, is found experimentally by real-time metal/glass observation and numerically by multi-physical modeling. Ex-situ X-ray fluorescence element mapping is used to characterize the element dilution status in the fusion zone. For the first time, the detrimental influence of the molten pool narrowing on the element transport is identified and discussed, combining the experimental and numerical results. A magnetohydrodynamic technique is utilized to suppress the narrowing, aiming at a more homogenous element distribution. It is found that due to the interaction of the two dominant circulations from the top and bottom regions of the molten pool, a low-temperature region is formed. It leads to an untypical growth of the mushy zone, narrowing the molten pool in the middle region. Its detrimental effect on material mixing is non-negligible considering the direct blocking effect on the downward flow and the premature solidification at the middle region. The Lorentz force from a transverse oscillating magnetic field can change the flow pattern into a single-circulation type. The downward transfer channel is widened, and its premature solidification is prevented because the low-temperature-gradient region is mitigated. This paper provides a supplementary reason regarding the common issue of insufficient material mixing during LBW, and a promising technique to optimize the process.